2009
DOI: 10.1152/ajplung.90505.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase cleaves VEGF to generate a VEGF fragment with altered activity

Abstract: Excessive neutrophil elastase (NE) activity and altered vascular endothelial growth factor (VEGF) signaling have independently been implicated in the development and progression of pulmonary emphysema. In the present study, we investigated the potential link between NE and VEGF. We noted that VEGF(165) is a substrate for NE. Digestion of purified VEGF(165) with NE generated a partially degraded disulfide-linked fragment of VEGF. Mass spectrometric analysis revealed that NE likely cleaves VEGF(165) at both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 80 publications
1
50
0
Order By: Relevance
“…In various studies, AAT has been shown to induce vascular endothelial growth factor (VEGF) production (55)(56)(57) and to prevent proteolytic degradation of VEGF (58). In addition, AAT was shown to facilitate smooth muscle myocyte migration and proliferation (59) and reduce endothelial cell and smooth muscle cell apoptosis (55,56,60,61).…”
Section: Binding Targets That Are Unrelated To Protease Inhibitionmentioning
confidence: 99%
“…In various studies, AAT has been shown to induce vascular endothelial growth factor (VEGF) production (55)(56)(57) and to prevent proteolytic degradation of VEGF (58). In addition, AAT was shown to facilitate smooth muscle myocyte migration and proliferation (59) and reduce endothelial cell and smooth muscle cell apoptosis (55,56,60,61).…”
Section: Binding Targets That Are Unrelated To Protease Inhibitionmentioning
confidence: 99%
“…More recently it has been shown to confer protection against injury and oxidative stress. This protection may be particularly important in the respiratory alveolus because pharmacological inhibition of VEGF activity and lung-targeted inactivation of the VEGF gene result in emphysematous phenotypes whereas VEGF expression diminishes emphysema in murine modeling systems (11,14,16,(32)(33)(34)49). In accordance with this finding, a number of investigators have reported decreased levels of VEGF expression/ accumulation in biological samples from patients with emphysema (16,33,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 74%
“…This may be clearly seen in the lung, where studies from our laboratory and others have demonstrated that VEGF overexpression induces tracheal angiogenesis, tissue edema, parenchymal inflammation, dendritic cell activation, airway fibrosis, mucus metaplasia, enhanced helper T-cell type 2 (Th2)-and IL-13-induced tissue responses and cytoprotection in the setting of oxidant injury (5,12). In accordance with these varied responses, normal lung development, baseline lung function, and the ability of the lung to respond to injury appear to be critically dependent on the presence of local functional VEGF (12)(13)(14)(15)(16). VEGF excess has been implicated in the pathogenesis of a variety of disorders including pulmonary edema and asthma (5,16,17).…”
mentioning
confidence: 99%
“…Thus, all evidence supports a Bvascular hypothesis^as a major feature of COPD pathophysiology (Henson et al 2006). Moreover, VEGFA may be partially cleaved by neutrophil elastase (NE), generating a VEGFA fragment with altered activities (Kurtagic et al 2009). The resulting binding by the altered receptor is translated to a loss of signaling potentials in endothelial cells and hinders lung vascular functions (Kurtagic et al 2009).…”
Section: Introductionmentioning
confidence: 86%